2001
DOI: 10.1128/mcb.21.15.5109-5121.2001
|View full text |Cite
|
Sign up to set email alerts
|

The TFIID Components Human TAFII140 andDrosophila BIP2 (TAFII155) Are Novel Metazoan Homologues of Yeast TAFII47 Containing a Histone Fold and a PHD Finger

Abstract: The RNA polymerase II transcription factor TFIID comprises the TATA binding protein (TBP) and a set of TBP-associated factors (TAF II s). TFIID has been extensively characterized for yeast, Drosophila, and humans, demonstrating a high degree of conservation of both the amino acid sequences of the constituent TAF II Transcription factor TFIID is one of the general factors required for accurate and regulated initiation by RNA polymerase II. TFIID comprises the TATA binding protein (TBP) and TBP-associated fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
86
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(92 citation statements)
references
References 58 publications
5
86
0
1
Order By: Relevance
“…Biochemical studies have also indicated that yTAF3 and yTAF8 contain HFDs that heterodimerize with a HFD in yTAF10 (33). A similar result was obtained in studies of their metazoan orthologues (21,34). The existence of these heterodimers in native yeast TFIID is supported by immunoelectron microscopy, which shows colocalization of these proteins (31).…”
supporting
confidence: 66%
“…Biochemical studies have also indicated that yTAF3 and yTAF8 contain HFDs that heterodimerize with a HFD in yTAF10 (33). A similar result was obtained in studies of their metazoan orthologues (21,34). The existence of these heterodimers in native yeast TFIID is supported by immunoelectron microscopy, which shows colocalization of these proteins (31).…”
supporting
confidence: 66%
“…In the case of MLL1, loss of MLL1 affects Pol II occupancy at target genes, possibly through a mechanism involving binding of H3K4me3 by the PHD domain of the TAF3 subunit of TFIID (Vermeulen et al, 2007). Interestingly, Arabidopsis lacks a TAF3 subunit (Lawit et al, 2007) and yeast TAF3 lacks a PHD finger (Gangloff et al, 2001), indicating that TAF3 tethering of PIC to H3K4me3 nucleosomes is not a general mechanism in all organisms. In further support of this difference, treatment with Flap or Selic CDK7/CDK9 inhibitors reduced H3K4me3 levels without reducing TBP occupancy at the three ATX1-dependent promoters examined ( Figure 7B).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the strict requirement of the YPWM motif to transform an eye into a wing, we screened for YPWM-motifspecific interacting co-factors. Employing the yeast two-hybrid system, we identified a novel Antp co-factor bric-à-brac interacting protein 2 (bip2), also referred to as dTAFII3 or TAFII155 (Gangloff et al, 2001), which specifically interacts with the YPWM motif of Antp in vitro and in vivo. Using gain-and loss-of-function approaches, we show that bip2 genetically interacts with Antp promoting dorsal ectopic wing development…”
Section: Introductionmentioning
confidence: 99%